2010
DOI: 10.1108/09654281011052655
|View full text |Cite
|
Sign up to set email alerts
|

Wellness 101: health education for the university student

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Wharf Higgins, Lauzon, Yew, Bratseth, and McLeod (2010) utilized a mixed method, two-phased approach in a study of wellness practices among Canadian university students and the impact of a 'Personal Health and Wellness' (PHW) course on student wellness practices. Using the standardized TestWell questionnaire, Phase I of the study revealed overall mean wellness scores of 779.7 out of 1,000 or "good" among the 855 primarily undergraduate students, with the highest scores reflected in sexuality and safety, and lowest in physical activity and nutrition.…”
Section: Wellness Coursesmentioning
confidence: 99%
“…Wharf Higgins, Lauzon, Yew, Bratseth, and McLeod (2010) utilized a mixed method, two-phased approach in a study of wellness practices among Canadian university students and the impact of a 'Personal Health and Wellness' (PHW) course on student wellness practices. Using the standardized TestWell questionnaire, Phase I of the study revealed overall mean wellness scores of 779.7 out of 1,000 or "good" among the 855 primarily undergraduate students, with the highest scores reflected in sexuality and safety, and lowest in physical activity and nutrition.…”
Section: Wellness Coursesmentioning
confidence: 99%
“…Their populations are comprised in large part of those aged 18-24 years, who represent both the youngest legal targets for tobacco industry marketing, and the age category with the highest smoking prevalence rates in Canada (Hammond et al 2005). Young adults beginning university also face psycho-social vulnerabilities as they transition to this context, potentially losing their previous support networks while encountering new external demands and time pressures (Colder et al 2006, Wharf Higgins et al 2010. These stressors may cause students to 'initiate compromised health behaviours that can persist throughout their lives' (Wharf Higgins et al 2010, p. 310).…”
Section: Campus Environmentsmentioning
confidence: 99%
“…Despite the many campus-based wellness programs and services offered, many U.S. students lack the strategies, skills, or support systems to manage stress or change pre-existing behaviors (Beauchemin et al, 2018;Wharf Higgins, Lauzon, Yew, Bratseth, & McLeod, 2010), resulting in unhealthy behaviors and poor overall wellness (Dubois, 2006). There is a need to continue to develop and design programs that increase students' wellness knowledge and behaviors (Nesbitt, 2012).…”
mentioning
confidence: 99%